Guter Unterricht in der zweiten Phase der Lehramtsausbildung Eine qualitativ-rekonstruktive Studie zum impliziten Unterrichts- und Professionsverständnis von Seminarleitenden - Wiernik, Alexander (Verlag Julius Klinkhardt, 2020)
This study examines the action-guiding orientations of teacher educators in the second period of teacher education with regard to their understanding of teaching, in particular the understanding of quality teaching and the role of teacher educators in the professionalisation process of the prospective teachers. The methodology of this study based on the qualitative-reconstructive research paradigm. The data were collected by narrative-based expert interviews and analysed by using the documentary method. Based on the findings it was possible to reconstruct different orientations towards the understanding of teaching on the one hand and different modes of action in teacher professionalisation on the other. Thereby teacher educators oscillate between good and effective teaching to evaluate lessons and consult teaching. In addition, different learning and educational understandings of the mentors could be reconstructed. This study remarks the complex actions of teacher educators characterised by different and multidimensional challenges. Based on the empirical results of this study a theory of the actions of teacher educators was developed. This study is part of teacher education research, empirical education research and general science of education. With this investigation the little explored second period of teacher education was examined focusing on practical experience of teacher educators thus making a markable contribution in teacher education in the second period of teacher education. (DIPF/Orig.)